Some Aspects of Plastic Strain in Chip Creation - Vasilko, Karol (Manufacturing Technology Journal, 2018)
The article presents an experimental method of tracking deformation domains in the formation of shavings in machining of metalical materials. The methodologies of the study of the mechanismus of lastic deformation in the zone of chip forming used hitherto were based on the observation of quasi-static states obtained by stopping the process of cutting. The methodology shown here rests in a dynamical study of the movement of grains or groups of grains in the area of chip forming. In the course of machining, the path of the movement of the particle is being recorded. This parth of the movement of the particle is being recorded. This part enables us to judge of the speed and the acceleration of the movement and draw some conclusions as to the course of the phenomena of the plastic deformation of the material in front of the cutting edge of the tool.
Keywords: machining; plastic deformation; hip forming